The dynamics of international competition : from practice to theory - Calori, Roland (Strategy series., 2000)
"This text provides a new framework for understanding international competitive systems and formulating international business strategy. It extends theories of industry-based global competition (Porter, Doz, Prahalad, Bartlett and Ghoshal) and explores the interactions between structural forces at the industry level and competitive actions at the firm level." "In this dialogue between practitioners and a group of researchers, business students will find both theoretical insights and practical methods, and scholars will find a case of organic theory built upon contextual practical knowledge."--Jacket.